Effect of exclusive breastfeeding and other infant and young child feeding practices on childhood morbidity outcomes: associations for infants 0-6 months in 5 South Asian countries using Demographic and Health Survey data - Saldana Hossain; Seema Mihrshahi (BMC, 2024)
Abstract Background Despite growing evidence of the impacts of exclusively breastfeeding infants during the first 6 months of life on preventing childhood infections and ensuring optimal health, only a small number of studies have quantified this association in South Asia. Methods We analyzed data from the Demographic and Health Surveys in Afghanistan (2015; n = 3462), Bangladesh (2017-2018; n = 1084), India (2019-2021; n = 26,101), Nepal (2022; n = 581), and Pakistan (2017-2018; n = 1,306), including babies aged 0-6 months. Multivariate logistic regression models were used to determine the association between exclusive breastfeeding in the last 24 h and diarrhoea, acute respiratory infections, and fever in the two weeks before the survey. We also examined the association between other infant and young feeding indicators and these outcomes. Results Infants who were exclusive breastfed had decreased odds of diarrhoea in Afghanistan (AOR: 0.49, 95% CI 0.35, 0.70), India (AOR: 0.80, 95% CI 0.70, 0.91), and Nepal (AOR: 0.42, 95% CI 0.20, 0.89). Compared with infants who were not exclusive breastfed, infants who were exclusively breastfed were less likely to have fever in Afghanistan (AOR: 0.36, 95% CI 0.26, 0.50) and India (AOR: 0.75, 95% CI 0.67, 0.84). Exclusive breastfeeding was associated with lower odds of acute respiratory infections in Afghanistan (AOR: 0.57, 95% CI 0.39, 0.83). Early initiation of breastfeeding was protective against diarrhoea in India. Bottle feeding was a risk factor for diarrhoea in India and for fever in Afghanistan and India. Bottle feeding was also a risk factor for acute respiratory infection in Afghanistan and India. Conclusions Not exclusive breastfeeding is a risk factor for diarrhoea, acute respiratory infections, and fever in some South Asian countries. These findings could have substantial implications for global and national efforts to increase exclusive breastfeeding rates. More support, advocacy, and action are required to boost breastfeeding rates as a crucial public health measure.